Orkut.com.escol@: currículos e ciborguização juvenil - Shirlei Rezende Sales (2010)
This thesis concerns about the production process of youthful subjectivities in interface between the technical public high school curriculum and Orkut curriculum (relationship entertainment site). For its developing, this research joined elements and procedures from ethnography, netnography and discursive analyze inspired in Foucault studies. The investigation was made based on Michael Foucault studies and on Culture Studies area, specifically post-criticism line, and query the youthful conduct spread, judged, reinforced or devaluated in the analyzed discourses. Based on post-structuralism perspectives, its analyzed the utilized strategies in subjectivation process of the connected youthful. The general argument from this thesis is about the interface between the school curriculum and the Orkut curriculum that engender a cyborguization process of youthful and have effects on the youth manners lead their conductions. The concept of cyborguization expresses not only the close relation youth-machine, but also shows particularly the ways of conduction the life, in which cultural borders are constantly questioned. By the negotiation sense spread on school curriculum and Orkut curriculum, the dispute and articulation between them, the invasion and overstep of borders, product different manners of being youth. On this thesis, It was analyzed the youth manners of act marked by gender, professionalization and sexuality signs. Although, the investigated discourses show several techniques and suggest exercises for the production of some youth subjectivities, that are infused of judgment value some good and bad things, some suitable and inappropriate things related with the conduct of each one and all- widely spread in our society and act in youth rule, there is also, in these discourses, several practices that escape, endure and conflict with the considered suitable manners. The thesis shows that, in the connection between the discourses of the school curriculum and Orkut, there is multiplicity of practices, techniques and strategies that sometimes are joined for compose the youth in a way, and sometimes dissent in the way they are showed. In face of it, the production process of youth subjectivities happens inside of power relations, which establish a batch of conflicts and disputes. This process has as an effect the production of multiple youth subjectivation possibilities, marked by provisionality, dynamism, fluidity, impermanence and also by contest, transgression and confusion of cultural borders. This thesis discusses, therefore, some youth subjectivities spread on the analyzed interface, like: cyborg; NERD; back classroom group; Dota female player; soccer female player; beautiful, stunning, dumb blond; the well-fit boy; the emotional boy; the electronic technician girl; straight male boy; the hard girl to get.